2012
DOI: 10.1161/hypertensionaha.111.181735
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Factors in Superimposed Preeclampsia

Abstract: Abstract-Imbalances in circulating angiogenic factors contribute to the pathogenesis of preeclampsia. To characterize levels of angiogenic factors in pregnant women with chronic hypertension, we prospectively followed 109 women and measured soluble fms-like tyrosine kinase 1 (sFlt1), soluble endoglin, and placental growth factor at 12, 20, 28, and 36 weeks' gestation and postpartum. Superimposed preeclampsia developed in 37 (34%) and was early onset (Ͻ34 weeks) in 9 and later onset (Ն34 weeks) in 28. Circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(57 citation statements)
references
References 34 publications
2
53
0
2
Order By: Relevance
“…With this approach, Moore Simas et al studied the high-risk population and achieved excellent diagnostic accuracy, calculating areas under the ROC curve for the sFlt-1/ PlGF ratio as 0.97 and for sFlt-1 as 0.90 for the prediction of early onset preeclampsia. Perni et al demonstrated in a longitudinal study of women with chronic hypertension that alterations in sFlt-1, PlGF, sFlt-1/ PlGF, and sEng were dramatically altered as early as 20 weeks of gestation in women who developed subsequent early onset preecalmpsia (51 ). Results have been more modest in other studies using angiogenic markers in high-risk populations (52,53 ).…”
Section: Angiogenic Factors In the Prediction Of Preeclampsiamentioning
confidence: 99%
“…With this approach, Moore Simas et al studied the high-risk population and achieved excellent diagnostic accuracy, calculating areas under the ROC curve for the sFlt-1/ PlGF ratio as 0.97 and for sFlt-1 as 0.90 for the prediction of early onset preeclampsia. Perni et al demonstrated in a longitudinal study of women with chronic hypertension that alterations in sFlt-1, PlGF, sFlt-1/ PlGF, and sEng were dramatically altered as early as 20 weeks of gestation in women who developed subsequent early onset preecalmpsia (51 ). Results have been more modest in other studies using angiogenic markers in high-risk populations (52,53 ).…”
Section: Angiogenic Factors In the Prediction Of Preeclampsiamentioning
confidence: 99%
“…Hence, the incorporation of angiogenic markers may help to risk stratify women with high suspicion for preeclampsia. Similarly, angiogenic markers have proved to be useful in distinguishing between confounding diagnoses, such as chronic hypertension, CKD, and lupus nephritis (12)(13)(14)(15). The potential to target sFlt as a therapy is also exciting and currently being studied using an apheresis technique (16).…”
Section: Angiogenic Factorsmentioning
confidence: 99%
“…A number of recent studies have suggested that circulating angiogenic factors in plasma or urine can be used to differentiate preeclampsia from other diseases that mimic preeclampsia such as chronic hypertension, gestational hypertension, lupus nephritis and gestational thrombocytopenia [47][48][49][50][51][52][53][54][55][56] . To demonstrate clinical utility, we prospectively studied the role of angiogenic biomarkers in the prediction of preeclampsia related adverse outcomes among women evaluated at our institution for suspected preeclampsia.…”
Section: Clinical Implications For Diagnosis and Treatment Of Preeclamentioning
confidence: 99%